Regulasi dan Perkembangannya dalam Ruang Sektor Publik - Luthfia Kurindra Fitri; Anissa Prameswari; Irene Rambu Padu Djabu (Jurnal Ekonomi, Akuntansi, dan Perpajakan, 2025)
Regulation plays an important role in the public sector as a legal foundation and reference in the implementation of governance. This article discusses regulation and its developments in the public sector of Indonesia, highlighting its functions, purposes, dynamics, and challenges in its implementation. Regulation aims to create legal certainty, enhance bureaucratic efficiency, protect public interests, and ensure the quality of public services. Over time, regulation has undergone significant changes, especially after the era of reform and digitalization, which has encouraged increased transparency through e-government and technology-based services. However, the implementation of regulations still faces obstacles such as overlapping rules, weak policy evaluation, and low public legal literacy. These challenges demand reforms that are not only normative, but also strengthen institutional capacity and public participation. Information technology is also an important tool to support adaptive and responsive regulations to the needs of the community. Through a literature review and policy analysis, this article concludes that sustainable regulatory reform is needed to support better, efficient, and public service-oriented governance that is fair and accountable.